2000
DOI: 10.1161/01.cir.101.19.2317
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Inhibits Irradiation- and Mannitol-Induced Apoptosis in Endothelial Cells

Abstract: Ang1 promotes the survival of endothelial cells in irradiation- and mannitol-induced apoptosis through Tie2 receptor binding and PI3-kinase activation. Pretreatment with Ang1 could be beneficial in maintaining normal endothelial cell integrity during intracoronary irradiation or systemic mannitol therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 25 publications
7
50
0
1
Order By: Relevance
“…First, we confirmed that in PRECs oxidative stress increases the number of apoptotic cells, which is consistent with previous findings (3). We then showed that Ang1 decreases the apoptotic cell number following oxidative stress, as is the case for other cellular stress inducers (25). Because caspase-3 is one of the key effectors of apoptosis and induces the proteolytic cleavage and activation of many apoptotic proteins, we elucidated that Ang1 also decreases the caspase-3 response to oxidative stress.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…First, we confirmed that in PRECs oxidative stress increases the number of apoptotic cells, which is consistent with previous findings (3). We then showed that Ang1 decreases the apoptotic cell number following oxidative stress, as is the case for other cellular stress inducers (25). Because caspase-3 is one of the key effectors of apoptosis and induces the proteolytic cleavage and activation of many apoptotic proteins, we elucidated that Ang1 also decreases the caspase-3 response to oxidative stress.…”
Section: Discussionmentioning
confidence: 69%
“…Ang1 has also been reported to induce specific effects, such as chemotactic responses through ShcA (22) and sprouting through either Dok-R or Akt activation (23). In addition, Ang1 has been demonstrated to be a potent survival factor against apoptosis induced by serum starvation (24), irradiation, and mannitol (25) through the activation of Akt in a PI 3-kinase-dependent manner. Tie2 also interacts with ABIN-2 in a ligand-dependent manner and inhibits NFB activity and concomitant endothelial cell death (26).…”
mentioning
confidence: 99%
“…These results suggest that the interaction between Tie2 receptor and the adapter protein ShcA may play a role in the regulation of migration and three-dimensional organization of ECs in response to Ang-1. Expression of ShcSH2 Does Not Affect the Protective Action of Ang-1 on EC Death-Ang-1 delays cell death associated with growth factor withdrawal or induced by irradiation or osmolarity changes (5,43,44). Consistent with the protective action of Ang-1 on ECs apoptosis are recent observations demonstrating that activation of the Tie2 receptor stimulates the recruitment of p85 regulatory subunit of PI 3-kinase and downstream action of the Akt signaling pathway (10,12).…”
Section: Inhibition Of Ang-1-stimulated Migration and Sprouting By Exmentioning
confidence: 83%
“…In this regard, Ang-1 behaves as both a survival (11,12,43,44) and a motility factor (4,11,33,42) and promotes EC sprout formation (6,42) and stabilization of tubule structures in collagen matrices (5). Following ligand binding, Tie2 receptor phosphorylates at three carboxyl-terminal tyrosine residues, which act as docking sites for a number of SH2-containing effectors (3,11).…”
Section: Discussionmentioning
confidence: 99%
“…Angiopoietin-1 (Ang1), the main ligand for Tie2 [18,19], and -4 [20] are agonistic ligands, whereas Angiopoietin-2 (Ang2) and -3 can serve as antagonistic ligands [20,21]. Although Ang1 does not stimulate proliferation of endothelial cells [18], in vitro Ang1 can induce endothelial migration [22], tubule formation [23] and sprouting [24,25], and survival from a variety of apoptotic insults [26][27][28][29], suggesting that Ang1 can be a potent pro-angiogenic factor. Transgenic null mutation of the Ang1 gene confirms an angiogenic role for Ang1, as Ang1 null embryos are unable to form a complex vascular network and exhibit decreased vessel support by mural cells [19].…”
Section: Angiopoietins and Tie2mentioning
confidence: 99%